Faktor Penyebab Kurang Efektifnya Penggunaan Alat Peraga dalam Pembelajaran Pengukuran Satuan Waktu pada Siswa Kelas V - Unaenah, Een; Aulia, Nabilah; Rahma, Salsa Nabila (MASALIQ, 2023)
The ineffectiveness of visual aids, particularly when teaching how to measure time, is the driving force for this study. This study intends to identify the factors that contribute to class V students' inability to learn unit time measures effectively when using instructional aids. The data collection procedures employed in this study are descriptive methods that involve observation, interviewing, and documentation throughout the course of a three-stage process._The_results_of_the_study_can be_seen_that_there_are_several problems that can hinder the effectiveness of the use of props. Based on interviews with teachers and students, the factors that cause these problems include_the_lack_of sufficient availability_of props, the_state of props that are damaged or not functioning, the lack of adequate explanations, limited learning time, lack of student motivation in learning to measure units of time, and lack of diversity in the use of props during learning.